Environmental enrichment enhances conditioned place preference to ethanol via an oxytocinergic-dependent mechanism in male mice. (August 2018) - Rae, Mariana; Zanos, Panos; Georgiou, Polymnia; Chivers, Priti; Bailey, Alexis; Camarini, Rosana
Abstract: Environmental conditions, such as stress and environmental enrichment (EE), influence predisposition to alcohol use/abuse; however, the underlying mechanisms remain unknown. To assess the effect of environmental conditions on the initial rewarding effects of alcohol, we examined conditioned place-preference (CPP) to alcohol following exposure to EE in mice. Since social context is a major factor contributing to initial alcohol-drinking, we also assessed the impact of EE on the levels of the "social neuropeptide" oxytocin (OT) and its receptor, OTR. Finally, we assessed the effect of pharmacological manipulations of the oxytocinergic system on EE-induced alcohol CPP. While EE increased sociability and reduced anxiety-like behaviors, it caused a ∼3.5-fold increase in alcohol reward compared to controls. EE triggered profound neuroadaptations of the oxytocinergic system; it increased hypothalamic OT levels and decreased OTR binding in the prefrontal cortex and olfactory nuclei of the brain. Repeated administration of the OT analogue carbetocin (6.4 mg/kg/day) mimicked the behavioral effects of EE on ethanol CPP and induced similar brain region-specific alterations of OTR binding as those observed following EE. Conversely, repeated administration of the OTR antagonist L, 369–899 (5 mg/kg/day) during EE exposure, but not during the acquisition of alcohol CPP, reversed the pronounced EE-induced ethanol rewarding effect. These results demonstrate for the first time, a stimulatory effect of environmental enrichment exposure on alcohol reward via an oxytocinergic-dependent mechanism, which may predispose to alcohol abuse. This study offers a unique prospective on the neurobiological understanding of the initial stages of alcohol use/misuse driven by complex environmental-social interplay. Highlights: Environmental enrichment (EE) and carbetocin enhance ethanol conditioned-place preference (CPP). EE and carbetocin decrease oxytocin receptor binding (OTR) in the PFC. EE increases oxytocin levels in the hypothalamus. Blockade of OTR during EE prevents EE-induced enhancement of ethanol CPP.